Arguments for utopias of reality and the Brazilian psychiatric reform experience - Braga, Cláudia (Saúde e Sociedade, 2020)
Political philosophy authors have argued that utopia and realism are distinct approaches to understand human relations and social problems, always in a state of constant tension, yet there are practical examples of utopias that became real experiences. Taking as starting point the experience of the Brazilian psychiatric reform in a theoreticalpractical perspective of deinstitutionalization, this study aimed to develop and present arguments to conceptually sustain the possibility of realizing utopias. An argumentative-reflective investigation was carried out on two topics – knowledge possibilities from an utopian position and the idea of problem in realism, interconnecting utopia and realism. The first argument focused on Spinoza’s approach to the kinds of knowledge, sustaining that a utopian position involves not only the imagination, but also reason and practices. The second argument proposes a shift in the understanding of the notion of problem in realism in order to comprehend it as contradictions that need to be kept open and dialectically confronted. Finally, based on a reading of Spinoza, hope and security are presented as the foundations sustaining the utopias of reality, in addition to reason and open contradictions.